Assessment of the prevalence and risk factors of ophthalmoplegia among diabetic patients in a large national diabetes registry cohort. Issue 1 (December 2016) - Al Kahtani, Eman; Khandekar, Rajiv; Al-Rubeaan, Khalid; Youssef, Amira; Ibrahim, Heba; Al-Sharqawi, Ahmed
Abstract Background There are limited data on the epidemiology and risk factors of ophthalmoplegia among diabetic patients. This study aims to determine the prevalence and important risk factors related to ophthalmoplegia among diabetic patients. Methods This is an observational registry-based study using the Saudi National Diabetes Registry (SNDR) database to select diabetic patients regardless of their diabetes type. A total of 64, 351 Saudi diabetic patients aged more than 18 years and registered in SNDR between January 2000 and December 2010 were analyzed to identify ophthalmoplegic cases. Demographic, clinical, and biochemical parameters were studied and STROBE guidelines were used to design and report the results of this study. Results The overall prevalence of ophthalmoplegia cases was 0.32 %, further distributed into: 53.11 %, 36.36 %, and 2.8 % for cranial nerves VI, III, IV palsies respectively. Ophthalmoplegic cases were predominantly type 2 diabetic males with older age and longer diabetes duration. The most important and significant risk factors were age ≥ 45 years, diabetes duration ≥ 10 years, male gender and presence of retinopathy and nephropathy. Conclusions Ophthalmoplegia is a rare entity associated mainly with type 2 diabetes. Clinicians have to consider its risk factors when screening or planning for prevention of this condition.